Physical determinants of daily physical activity in older men and women. - Laura Karavirta; Timo Aittokoski; Katja Pynnönen; Timo Rantalainen; Kate Westgate; Tomas Gonzales; Lotta Palmberg; Joona Neuvonen; Jukka A Lipponen; Katri Turunen; Riku Nikander; Erja Portegijs; et al. (PLoS ONE)
Introduction The ability to perform bodily movement varies in ageing men and women. We investigated whether physical fitness may explain sex differences in daily physical activity energy expenditure (PAEE) among older people. Methods In this cross-sectional study, a population-based cohort of 75, 80, and 85-year-old men and women (n = 409, 62% women) underwent laboratory-based assessment of walking speed, maximal knee extension strength, and body fat percentage. Free-living physical activity was assessed as total PAEE, and light (LPA) and moderate-to-vigorous physical activity (MVPA) using individually calibrated combined accelerometry and heart rate sensing. Path modelling was used to examine indirect associations between sex, physical fitness, and physical activity. Results Men had better physical fitness and higher overall PAEE (mean 34.0 (SD 10.8) kJ/kg/day) than women (28.3 (8.4) kJ/kg/day, p<0.001). The path model for PAEE explained 33% of the variance. The direct association between sex and PAEE was non-significant, whereas the association between sex and PAEE mediated by body fat (β = 0.20, p<0.001) and walking speed (β = 0.05, p = 0.001) were statistically significant. Similarly, associations between sex and MVPA mediated by body fat (β = 0.11, p = 0.002) and walking speed (β = 0.05, p = 0.001) were significant, as were the associations between sex and LPA mediated by body fat (β = 0.24, p<0.001) and walking speed (β = 0.03, p = 0.019). Conclusion Differences in physical activity between men and women may reflect underlying differences in cardiorespiratory fitness and adiposity. These results highlight the importance of maintaining physical fitness to support active living in older adults.